S1 guidelines: Tinea capitis. (6th February 2020) - Mayser, Peter; Nenoff, Pietro; Reinel, Dieter; Abeck, Dietrich; Brasch, Jochen; Daeschlein, Georg; Effendy, Isaak; Ginter‐Hanselmayer, Gabriele; Gräser, Yvonne; Hipler, Uta‐Christina; Höger, Peter; Kolb‐Mäurer, Annette; et al.
Summary: Tinea capitis describes a dermatophyte infection of scalp and hair that predominately occurs in children. The diagnostic workup includes microscopic examination, culture and/or molecular tests. Treatment is guided by the specific organism involved and should consist of systemic agents as well as adjuvant topical treatment. The aim of the present update of the interdisciplinary German S1 guidelines is to provide dermatologists, pediatricians and general practitioners with a decision tool for selecting and implementing appropriate diagnostic and therapeutic measures in patients with tinea capitis. The guidelines were developed based on current international guidelines, in particular the 2010 European Society for Pediatric Dermatology guidelines and the 2014 British Association of Dermatologists guidelines, as well as on a review of the literature conducted by the guideline committee. This multidisciplinary committee consists of representatives from the German Society of Dermatology (DDG), the German‐Speaking Mycological Society (DMykG), the German Society for Hygiene and Microbiology (DGHM), the German Society of Pediatric and Adolescent Medicine (DGKJ) and the German Society for Pediatric Infectious Diseases (DGPI). The Division of Evidence‐based Medicine (dEBM) provided methodological assistance. The guidelines were approved by the participating medical societies following a comprehensive internal and external review.